Classification of Lending Risks and Interpretation of Operational Efficiency in Islamic Banks Registered on the Bahrain Stock Exchange - Shaalan, Tharwah (International Journal of Economics and Financial Issues, 2018)
This paper aims to classify the credit risk and interpret the operational efficiency for Islamic banks listed on the Bahrain Stock Exchange (BSE). The paper is divided into two parts. Part I relates to classifying the risk of lending via a range of variables: lending ratios, loan profitability, and bank risk variables such as capital bank adequacy and financial leverage. Discriminant analysis has been used to prove the hypothesis in this section. Part II relates to the interpretation of operational efficiency via a set of variables reflecting the bank’s ownership, number of branches, financial leverage, and the size of the bank. The hypothesis here was proven by using a random regression effects analysis. The regression results reflected the impact of the mentioned variables on the operating efficiency for Islamic banks listed on the BSE. The study is structured as follows: Introduction; Models of forecasting financial failure; Review of literature on the efficiency of banks; Hypothesis of part 1,which classifies Islamic banks into three categoriesâ€”low, medium, or highâ€”based on the banks’ efficiency including hypotheses tests, description of variables, and the mathematical model; Results of hypotheses of part I; Hypotheses of part II, which is devoted to testing the efficiency of Islamic banks using the explained variables and the same methodology as in part I; Results of part II; Conclusion; and References. Keywords: loans profit efficiency, Islamic Banks, Z-scores, operating efficiency, classification. JEL Classifications: C33, C38, G21 DOI: https://doi.org/10.32479/ijefi.7114